Up-to-date laboratory methods for assessing the safety of perfumery and cosmetic products in the quality assurance system of the Russian Federation - A. V. Rezaykina; N. P. Petrova; S. V. Rotanov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Most of the developed countries as well as Russian Federation have a dynamically developing quality assurance system for testing the quality of laboratory tests and safety of perfumery and cosmetic products entering the market comprising a regulatory and legal framework, physical infrastructure and appropriate methodical basis and staff. At the same time, it is necessary to develop alternative test methods adjusted to perfumery and cosmetic products on a regular basis. In addition, it is necessary to optimize methods for ensuring standard sample preparation conditions in response to new forms of cosmetic products when determining microbiological, physical, chemical and toxicological characteristics, and more accurate observation methods for clinical and laboratory indices to be approved by supervising authorities.